Analisis Dilema Diskusi di Era Digital, Ruang Publik atau Arena Konflik: (Analisis Habermas dalam Kasus Amsal Sitepu Pada Platform X) - Siti Patimah; Irfan Haniful Qoyyim; Feggy Nurdiansyah; Dono Darsono (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
This research aims to analyze the phenomenon of digital discourse on platform X in the Amsal Sitepu case through the lens of Jürgen Habermas's Public Sphere theory. The criminalization of videographer Amsal Sitepu triggered massive debates that blurred the boundaries between rational-critical dialogue and emotional conflict arenas in cyberspace. Using a descriptive qualitative method and a critical discourse analysis approach, this study explores how platform X functions as a contemporary public sphere. The results show that although digital platforms are often trapped in opinion fragmentation, particularism, and affective conflict, the Amsal Sitepu case proves the existence of emancipatory potential through the "communicative power" of civil society. Organized public opinion pressure on social media proved capable of demanding institutional accountability and correcting the dominance of administrative power. This study concludes that social media can become an effective public sphere if the established discourse is able to transform from mere sentiment into logical and measured arguments.